Stat.Edu'21 - New Perspectives in Statistics Education. Proceedings of the International Conference Stat.Edu'21 - Davino, Cristina (Fuori collana, 2022)
The volume collects the papers presented at the Conference "Stat.Edu'21 -New Perspectives in Statistics Education". The Conference was held at the Department of Political Sciences of the University of Naples Federico II (25-26 March 2021). The conference was the final event of the "ALEAS - Adaptive LEArning in Statistics", an ERASMUS+ project (https://aleas-project.eu) developed in the period 2018-2021 to design and implement an Adaptive LEArning system able to offer personalised learning paths to students, with the purpose to provide them remedial advice to deal with the "statistics anxiety". Stat.Edu'21 aimed at stimulating discussions, solicitations and contributions around the central theme of ALEAS, the development of adaptive learning systems in the field of Higher Education as a complementary tool for traditional courses and promote a community of practice in this field. The volume collects 12 papers reporting reflections and quantitative studies covering mainly three topics: the assessment of the effects of anxiety or more generally of a different attitude in the study of Statistics, tools and methods for the assessment of training paths and technology-based learning experiences